Applying Fixed Effects to Hierarchical Segregation Models - Shatnawi, Dina; Oaxaca, Ronald; Ransom, Michael (American Economic Review, 2011)
This paper expands the empirical implementation of hierarchical segregation models to allow for the use of panel methods. We use firm level data collected between 1977 and 1985 from a regional grocery store that faced a title VII class-action lawsuit over gender discrimination much the same as Wal-Mart and Costco. Special problems arise in implementing decompositions in a fixed effects and random effects setting, especially when analyzing wage-level differences. We develop a variation of wage decompositions that takes into consideration an unbalanced design and extends the literature by explicitly formalizing the inclusion of the unobserved heterogeneous effects.